2022
DOI: 10.1128/mbio.02319-22
|View full text |Cite
|
Sign up to set email alerts
|

Accessing the Variability of Multicopy Genes in Complex Genomes using Unassembled Next-Generation Sequencing Reads: The Case of Trypanosoma cruzi Multigene Families

Abstract: Sequences that have several copies in a genome, such as multicopy-gene families, mobile elements, and microsatellites, are among the most challenging genomic segments to study. They are frequently underestimated in genome assemblies, hampering the correct assessment of these important players in genome evolution and adaptation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…In order to find immunodominant epitopes, the frequency in which the same peptide appeared in the top score for different HLA-ABC alleles was analyzed. Because T. cruzi has a high genetic diversity between strains, especially in the TS multigene family 42 , we also looked for conserved immunogenic epitopes among different discrete typing units (DTUs) (Supplementary Tables 1 , 2 ). Using these strategies, it was possible to detect potentially immunogenic regions in both proteins.…”
Section: Resultsmentioning
confidence: 99%
“…In order to find immunodominant epitopes, the frequency in which the same peptide appeared in the top score for different HLA-ABC alleles was analyzed. Because T. cruzi has a high genetic diversity between strains, especially in the TS multigene family 42 , we also looked for conserved immunogenic epitopes among different discrete typing units (DTUs) (Supplementary Tables 1 , 2 ). Using these strategies, it was possible to detect potentially immunogenic regions in both proteins.…”
Section: Resultsmentioning
confidence: 99%
“…It was previously observed that for the same amount of parasite DNA, TcI strains had higher Ct values than TcII, which would correspond to a lower number of satDNA copies of the former DTU [ 31 , 39 , 51 , 52 ]. In fact, recent findings have described that the size of the T. cruzi mitochondrial and nuclear genome and the content of chromosomes and multigene families vary in sequence and content among the parasite’s strains, even those classified into the same DTU or between different DTUs [ 53 , 54 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…The spot intensity of each peptide was quantitatively measured by densitometry scanning analysis using the software Image J–Protein Array Analyzer plug-in ( http://image.bio.methods.free.fr/ImageJ/?Protein-Array-Analyzer-for-ImageJ.html ) as described elsewhere ( Reis-Cunha et al, 2022 ). Briefly, densitometry values were normalized and the mean densitometric value of the four less reactive peptides from each experiment was subtracted from the densitometric value of each spot of the same membrane.…”
Section: Methodsmentioning
confidence: 99%